Hypermutable hotspot enables the rapid evolution of self/non-self recognition genes in Dictyostelium - Mische Holland; Mayar Ahmed; Janet M. Young; James R. Drurey; Sean McFadyen; Elizabeth A. Ostrowski; Tera C. Levin (Proceedings of the National Academy of Sciences, 2025)
Cells require highly polymorphic receptors to perform accurate self/non-self recognition. In the amoeba Dictyostelium discoideum , polymorphic TgrB1 and TgrC1 proteins are used to bind sister cells and exclude cheaters, but it remains unknown how cells continually generate their extreme genetic diversity. Here, we created a collection of chromosome-length, whole genome sequences from 10 D. discoideum isolates and sister species to understand the evolution of the large tgr gene family. Our dataset includes AX2-214, a widely used D. discoideum lab strain, as well as complete genomes for two Chlamydia -like endosymbionts harbored within amoebae. We find that tgrB1 and C1 lie in a hypermutational hotspot, with haplotypes that undergo repeated intralocus recombination, duplications, transpositions, and inversions. These structural dynamics are highly localized adjacent to tgrB and C , resulting in the gain and loss of dozens of genes. The tgrBC genes themselves frequently duplicate and recombine, leading to the rapid generation of unique tgrBC repertoires. In the broader tgr gene family, some genes (e.g., tgrN ) are single copy and syntenic across all the genomes, whereas others (e.g., tgrA ) prolifically duplicate at similar rates to Dictyostelium transposons. Thus, the tgr genes are among the most rapidly evolving families genome-wide. We propose that the intense diversification within the tgrBC locus can help explain how these genes acquire such extreme levels of polymorphism, with parallels to the MHC immune genes in mammals and other allorecognition systems. This collection of amoeba genomes is also a useful resource for future comparative genomics and molecular evolution studies in Amoebozoa.